Determination of Dutasteride from its Bulk Drug and Pharmaceutical Preparations by High Performance Thin Layer Chromatography - Kamat, S.S.; T. Vele, Vinayak; C. Choudhari, Vishal; S. Prabhune, Swarup (Asian Journal of Chemistry, 2010)
A rapid, simple and sensitive high-performance thin layer chromatographic method (HPTLC) has been developed to assay dutasteride in capsules. The HPTLC analysis used a normal phase (silica gel 60 F254) as a stationary phase and a mobile phase consisting of mixture of acetonitrile:glacial acetic acid with UV detection at 210 nm. The validation data showed that the assay is sensitive, specific and reproducible for determination of dutasteride in this dosage form. Calibration curves were linear from 50-500 μg mL-1 (R2 > 0.998). The accuracy of the method ranged from 99.17 to 99.94 %. Mean inter- and intra-assay relative standard deviations (RSD) were less than 2 %. The proposed method provided an accurate and precise analysis of dutasteride in its pharmaceutical preparations.